A Virtual Museums and 3D Artefacts to Improve Cultural Heritage Education - Bagus Satria; Fajar Ramadhani; Syafei Karim; Nur Aini (Politeknik Pertanian Negeri Samarinda, 2023)
In the current era of globalization and modernization, the imperative to safeguard and convey cultural heritage and history to society becomes increasingly significant. Web-based virtual museums have emerged as a pivotal solution, facilitating the preservation and promotion of cultural heritage on a global scale. These virtual platforms offer visitors unprecedented access to artifact collections, transcending the limitations of physical museum visits. The immersive features, such as the ability to view objects from diverse angles and zoom in on intricate details, present a profound and engaging experience. This research is to contribute insights into the development of effective web-based virtual museums featuring 3D artifact representations, thereby making a meaningful contribution to the broader field of cultural heritage preservation. The primary objective of this study is to enrich the exploration and learning experiences of visitors in the realm of cultural heritage through digital platforms. The research employs a structured software development methodology encompassing vital stages like needs analysis, system design, implementation, testing, and maintenance. By focusing on the technological aspects, the study seeks to address challenges related to quality and reliability faced by web-based virtual museums. Furthermore, the findings aim to enhance the overall effectiveness of these museums in offering a comprehensive and captivating journey through cultural artifacts. This research is poised to not only advance the field of virtual museum development but also foster a deeper appreciation and understanding of our rich cultural heritage.